The Psychometric Properties of the Norwegian version of Wechsler Intelligence Scale for Children, Fifth Edition (WISC-V) - Brøndbo, Per Håkan; Egeland, Jens (PsykTestBarn, 2019)
Description: Wechlser Intelligence Scale for Children – Fifth Edition (WISC-V) was published in the USA in 2014, and a Norwegian version was published in 2017. The Norwegian and international owner is Pearson Assessment. Translation, including cultural adaptation, was performed by Pearson Assessment, with assistance from clinical expertise in Norway, Denmark and Sweden. WISC-V is an individually administered test of intellectual abilities for children and youth aged 6:0-16:11 years. The test consists of 15 subtests, where ten are primary and five are secondary tests. Estimated test time is 45-80 minutes, dependent on the number of subtests and the age of the child. Psychologists or professionals with a master’s degree in education from the University of Oslo are qualified for purchasing the test, and there is a licensing program available for professionals with a master’s degree in education from other universities as well as for master’s in psychology. Literature search: The search found 1119 Norwegian, and 1865 Swedish and Danish hits. None of them relevant. The Scandinavian norms from the manual is the only available material for the evaluation of the psychometrics. Age-group norms, validity and reliability, in addition to mean scores for gifted children, and children with minor learning disabilities, were reported. Psychometric: Norm data from 660 children 6:0 until 16:11 were reported. Results were presented as scaled scores ranged 1 to 19, with a mean of 10 and a standard deviation of 3. Index scores were constructed with a mean of 100, standard deviation of 15, and range 45-155, respectively 40-160. Internal consistency for subtests and indexes were good to excellent. Goodness-of-fit-analyses for confirmatory factor analyzes gave CFI 0,97-0,98 and RMSEA 0,05 for the chosen five-factor model. The pattern of inter-correlations between sub-tests, process scores and indexes were mostly similar to the US standardization. Corrected rank correlation for FSIQ and indexes between WISC-V and WISC-IV are high (0,67-0,91). Criterion validity for predicting minor learning disability and giftedness were poorer than expected, especially for identifying gifted children. Conclusion: More documentation of the psychometrics in a clinical Scandinavian context is needed. Based on the available documentation, WISC-V mainly seems as a reliable instrument of intelligence assessment and assessment of cognitive profiles. It is not enough available data to evaluate if WISC-V also is a valid instrument, especially for assessment of cognitive profiles. Clinical interpretation of cognitive profiles should therefore be done with caution.